2013
DOI: 10.3899/jrheum.121145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Enthesitis on 1505 Brazilian Patients with Spondyloarthritis

Abstract: The clinical presence of enthesitis in this large cohort of patients with SpA was frequent and was associated with a significant increase in disease activity and decline in functional capacity and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 42 publications
3
17
1
3
Order By: Relevance
“…Most patients in our study had up to 2 tender enthesitis sites. This number is similar to the INSPIRE study, which reported a median of 1.8 enthesitis sites among PsA patients, and to another study that reported a mean of 2.1 affected entheseal sites among a large study (1,505 participants) of heterogeneous SpA patients . Interestingly, bilateral involvement was detected in up to one‐fifth of the patients with enthesitis.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Most patients in our study had up to 2 tender enthesitis sites. This number is similar to the INSPIRE study, which reported a median of 1.8 enthesitis sites among PsA patients, and to another study that reported a mean of 2.1 affected entheseal sites among a large study (1,505 participants) of heterogeneous SpA patients . Interestingly, bilateral involvement was detected in up to one‐fifth of the patients with enthesitis.…”
Section: Discussionsupporting
confidence: 87%
“…A lower prevalence was detected in population‐based studies from Iceland (8%) and Olmstead County (23%) . A higher prevalence of enthesitis (53.8%) was reported from a multicenter SpA study . These discrepancies can be attributed to the use of different enthesitis indices.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Symptoms resembling enthesitis (i.e., pain/ swelling of heel) were reported by 31% of patients, and symptoms resembling dactylitis (i.e., ''sausage'' digits) were reported by 45% of patients. Enthesitis and dactylitis, important distinguishing features of PsA in many patients, are associated with more severe disease; both can be difficult to treat and can lead to disability [5,13,31]. Approximately twice as many patients with PsA (21%) had nail involvement compared with patients with psoriasis alone (11%), and 44% of patients with PsA reported scalp involvement; however, overall these rates are lower than those previously reported [8,17,18,21,26].…”
Section: Discussioncontrasting
confidence: 48%
“…Physical examinations should be relevant to the patient's predominant presenting features, but all patients should have a tender joint count, swollen joint count, and entheseal assessment (LOE IV, SOR D). Enthesitis in SpA has been associated with poorer outcomes and increased disease activity 29,30 . Specific metrology of the spine is not included because the clinical utility and prognostic value of spinal metrology remains under study (LOE IV, SOR D).…”
Section: Disease Monitoringmentioning
confidence: 99%